MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 3-4 TAHUN MELALUI MEDIA VIDEO ANIMASI DI KB ASOKA CERIA MARON TAHUN PELAJARAN 2025/2026 - Yuni Anggit Aulia; Ianatuz Zahro; Adzkiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking is the ability to produce articulate sounds or words to express, convey, and convey thoughts, ideas, and feelings. Children aged 3-4 years are generally able to receive and understand language, are able to listen to conversations, and enjoy listening to and retelling simple stories in an easy-to-understand sequence. While development occurs naturally, appropriate stimulation is essential for optimal development of speaking skills. The challenge is how to provide effective and engaging stimulation for children of this age. The purpose of this research is to improve speaking skills through animated videos. The specific objectives of this research are the ability to pronounce words clearly, to string together 3-5 words into a sentence, and to begin using words to express basic emotions such as happiness, sadness, or anger. The method used is Classroom Action Research (CAR) using the Kemmis model, a spiral cycle consisting of four stages: planning, action, observation, and reflection. This cycle repeats continuously until the research objectives are achieved, where the results of the reflection will form the basis for planning the next cycle, which aims to refine and improve learning practices. The expected benefits of this research are to encourage teachers to increase the use of video media for early childhood and to encourage children's speaking skills according to their developmental level in a fun way. Therefore, this study can be concluded that animated video media successfully improves the speaking skills of children aged 3-4 years.